Clinicopathologic Features of Diencephalic Neuronal and Glioneuronal Tumors. Issue 1 (10th December 2019) - Ho, Cheng-Ying; Bornhorst, Miriam; Almira-Suarez, M Isabel; Donev, Kliment; Grafe, Marjorie; Gordish-Dressman, Heather; Rodriguez, Fausto J
Abstract: Neuronal/mixed glioneuronal tumors are central nervous system neoplasms composed of neoplastic neuronal cell components or a mixture of glial and neuronal elements. They occur in cerebral hemispheres, posterior fossa, and spinal cord. Compared with other tumors at these locations, diencephalic neuronal/glioneuronal tumors are very rare and therefore not well characterized. We hereby performed clinicopathologic evaluation on 10 neuronal/glioneuronal tumors arising from the diencephalic region. Morphologically, these tumors resemble their histologic counterparts in other locations, except that lymphocytic infiltrates and microcalcifications are more common than Rosenthal fibers or eosinophilic granular bodies. The BRAF V600 mutation rate is 75%. Given the high percentage of samples being small biopsy specimens, the subtle histologic features and molecular findings greatly aided in establishing the pathologic diagnosis in several cases. At a median follow-up of 42 months, 71% of the tumors demonstrated radiological recurrence or progression, with median progression-free survival of 18 months. Recurrence/progression is observed in tumors across different histologic subtypes, necessitating additional therapies in 56% of the cases. Despite their bland histology, diencephalic neuronal/glioneuronal tumors are not clinically indolent. Their frequent recurrences warrant a close follow-up, and the prevalent BRAF mutation makes MAPK pathway inhibition a plausible treatment option when conventional therapies fail.